Pemanfaatan Media Sosial Sebagai Edukasi Agama Dikalangan Mahasiswa Teknik Industri UPN “Veteran” Jawa Timur - Arya M. Shakti; Rizky N. Hidayah; Rangga D. Syahputra; Trianisa Muniroh; Nazwa R. Armevia; Erwin Kusumastuti (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2024)
Students have broad and easy access to various social media platforms, this opens up opportunities for educational institutions and parties involved in the field of religious education to utilize social media as a means of spreading religious values. However, the use of social media in the context of religious education is not without challenges, various aspects such as the accuracy of information, privacy, and the potential for polarization of views are things that need to be considered seriously. To solve the problems faced, the method of distributing questionnaires to students was used, to determine the level of effectiveness of using social media as a means of religious education. The data obtained will be analyzed using validity and reliability tests to find out whether the data can be said to be valid and reliable with the help of SPSS software. Based on the results of the research that has been conducted, it can be concluded that the level of effectiveness of using social media as a means of religious education is high, a number of positive responses from the majority of respondents is proof that social media helps them in studying and understanding religion. The variable data used is declared valid because it has a calculated r value > r table and a significance value < 0.05. Apart from that, the variable data was also declared reliable because it had a Cronbach's alpha value > 0.6. This research aims to analyze the level of effectiveness of using social media as a means of religious education.